ChemInform Abstract: A Facile One‐Pot Synthesis of Substituted Quinolines via New Multicomponent Reaction. Issue 6 (20th February 2013) - Rineh, Amir; Khalilzadeh, Mohammad A.; Hashemi, Mohammad M.; Rajabi, Medi; Karimi, Fatemeh
Abstract Quinoline derivatives (IV), (VI) are efficiently obtained in a one‐pot three‐component reaction of alkyl 4‐chloroacetate or ethyl chloropyruvate and activated acetylenic compounds in the presence of the nucleophilic form of isatin in water.